PsycEXTRA Dataset 2004
DOI: 10.1037/e524332011-061
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with the outpatient encounter: A comparison of patients' and physicians' views

Abstract: OBJECTIVE:To compare patients' and physicians' visit-specific satisfaction in an internal medicine outpatient setting, and to explain their respective views. DESIGN:Patients' and physicians' background characteristics were assessed prior to outpatient encounters. Immediately after the encounter, both patients and physicians completed a questionnaire assessing satisfaction with the visit. SETTING:The outpatient division of an academic teaching hospital. PARTICIPANTS:Thirty residents and specialists in general i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 18 publications
2
71
1
1
Order By: Relevance
“…This study demonstrates that involving patients in decisions about their care has a statistically significant effect on their satisfaction. This has been demonstrated by several studies and is a key attribute of the patient-centered consultation method [15][16][17]. Involving the patient does not mean all decisions must be 'ratified' by the patient but it does mean that he should be fully aware of the reasons for the decision and the available options.…”
Section: Involving the Patient In Decisions About The Carementioning
confidence: 99%
“…This study demonstrates that involving patients in decisions about their care has a statistically significant effect on their satisfaction. This has been demonstrated by several studies and is a key attribute of the patient-centered consultation method [15][16][17]. Involving the patient does not mean all decisions must be 'ratified' by the patient but it does mean that he should be fully aware of the reasons for the decision and the available options.…”
Section: Involving the Patient In Decisions About The Carementioning
confidence: 99%
“…This discrepancy may cause frustration on both sides if not dealt with sensitively. Professionals may not be able to judge which patients are less satisfied with the care they are receiving as doctor satisfaction levels following consultation are not correlated with patient satisfaction levels (Zandbelt et al 2004). There is also no correlation between doctors' perception of patient satisfaction and patients' actual satisfaction scores (Merkel 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Other Authors' presented a similar position on the issue. They observed that the more empathy from the medical personnel the better the patients' assess their competence, and consequently are more satisfied with the hospitalization and treatment (13,26,28,(38)(39)(40)(41)(42). Satisfying the patients' emotional needs is an important element of medical care provided to patients subject to surgical treatment.…”
Section: Discussionmentioning
confidence: 99%